Physical chemistry for engineering and applied sciences - Foulkes, F. R. (Boca Raton : CRC Press, Taylor & Francis Group, 2013)
'PREFACE Welcome to Physical Chemistry for Engineering and Applied Sciences! This course has been running for many years (I took it myself as a first year engineering student in 1961, and, in spite of the fact that I wasn't the sharpest tool in the shed, I seem to have passed it, so I guess it can't be all that tough). Most first year university physical chemistry textbooks have been designed more for students in chemistry than for students in engineering and applied sciences. These books tend to be more theoretical than what the rest of us require. Frankly, freshman students in engineering and the applied sciences don't need to know too much at this stage about quantum mechanics, atomic structure, and molecular spectroscopy. But they do need to know about melting points, how to balance a chemical reaction, and how to calculate the voltage of a car battery. For years my colleagues had been saying that we really ought to write our own textbook. So..... here it is! It may not be perfect,1 but at least it doesn't cost $200, and it doesn't contain a lot of stuff that's not relevant to what you need to know, and it's small enough that it can almost be carried around and read on the subway. When I was an undergraduate student there was one thing that especially bugged me about almost all the assigned textbooks for our various courses: I could almost never follow the derivations of the equations! The authors of these books would write down some equation, and then, skipping about 20 steps, say something like:'It is readily shown that, after simplification, equation [1] reduces to equation [2].' Huh? I remember wasting whole days on the weekends trying to figure out how we get to equation [2] from equation [1]'--
Includes bibliographical references and index.
Keywords: Chemistry, Physical and theoretical -- Textbooks